Assessment of the relationship between building density and urban heat island using Landsat images in Makassar City. Issue 1 (June 2021) - Ridwan,; Rasyidi, E S; Syafri,; Rahman, R; Okviyani, N; Jumadil,; Ma'rief, A A
Abstract: Increasing temperatures in urban areas provide many adverse effects, and such is the potential for fires, air pollution up to the comfort of life in the state capital, and the other problems, with the global warming which occurred in the world, such as the melting of ice on most of the north pole, unpredictable Global warming and the number of flora and fauna habitat damaged. The need for facilities and infrastructure is the main factor that triggers settlements' development; in general, urban areas often experience densely populated settlements. Therefore, researchers feel the need to monitor the relationship between Urban Heat Island (UHI) in Makassar City. Monitoring of Urban Heat Island needed surface temperature data from Landsat 8 OLI/TIRS with a thermal band resolution of 100m, building density needed NDBI models for data building density. This study analyses the relationship between building density and urban Heat Island using Landsat Imagery Data in Makassar city. The Landsat 8 OLI/TIRS imagery provides to be used to show the Urban Heat Island (UHI) phenomenon in Makassar City. In addition to UHI analysis, Landsat 8, Oil/TIRS imagery provides building density information using the NDBI spectral transformation. The results of the two result models' determination tests show that Urban Heat Island and Building Density have a very high relationship.